2015
DOI: 10.1111/jog.12670
|View full text |Cite
|
Sign up to set email alerts
|

p53 expression in breast cancer predicts tumors with low probability of non‐sentinel nodes infiltration

Abstract: p53 expression in breast cancer was highly predictive of non-sentinel lymph node negativity in our study. New studies should evaluate if it would be useful to add p53 expression to other existing predictive tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…We concluded that a p53 positivity burden together with a high histological grade were associated with a low axillary tumor load. This conclusion is consistent with the results of our previous study . Positive p53 breast cancers, although aggressive, could explain low axillary involvement because they would mainly start hematological dissemination during tumor growth .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We concluded that a p53 positivity burden together with a high histological grade were associated with a low axillary tumor load. This conclusion is consistent with the results of our previous study . Positive p53 breast cancers, although aggressive, could explain low axillary involvement because they would mainly start hematological dissemination during tumor growth .…”
Section: Discussionsupporting
confidence: 93%
“…This conclusion is consistent with the results of our previous study. 18 Positive p53 breast cancers, although aggressive, could explain low axillary involvement because they would mainly start hematological dissemination during tumor growth. 19 In the present study, significant differences were observed in bivariate analysis but not in multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that higher EpCAM expression was correlated with high Ki67 expression and low p53 expression. It is well known that p53 is the tumor suppressor and has many mechanisms of anticancer function, and plays a role in apoptosis, genomic stability, and inhibition of angiogenesis [ 17 , 18 ]. Ki-67 is a tumor marker that is found in growing, dividing cells.…”
Section: Resultsmentioning
confidence: 99%
“…The prognostic and predictive value of p53 expression in axillary lymph node metastasis in patients with breast carcinoma needs to be further evaluated in larger trials with longer follow-up (Arun et al, 2003). A number of studies reported that the expression of p53 had direct correlation with tumor size (Osanai et al, 2005), histological grade (Qing et al, 2014;Osanai et al, 2005;Sirvent et al, 1995;Bertheau et al, 1998), nuclear grade (Jasar et al, 2015, lymph-vascular invasion (Osanai et al, 2005), the proliferation index Ki67 (Jasar et al, 2015) and ER status (Osanai et al, 2005;Li et al, 2015), but other studies showed that the expression of p53 had inverse correlation with histological grade (el-A Helal et al, 2000), lymph-vascular invasion (Jasar et al, 2015), non-sentinel lymph node invasion (Vernet et al, 2015) and estrogen (Sirvent et al, 1995) and progesterone receptors (Sirvent et al, 1995;Bertheau et al, 1998). Also, a number of studies reported that there was no significant correlation between the expression of p53 and age (Qing et al, 2014), clinical stage (Qing et al, 2014), or lymph node metastasis (Sirvent et al, 1995;Sjostrom-Mattson et al, 2009;Qing et al, 2014) in the BC.…”
Section: Discussionmentioning
confidence: 99%